A Comprehensive Systematic Review of The Role of Ketamine-Propofol (Ketofol) in Interventional Radiology Oncology - Nadya Larasati; Ashri Mirawati (International Medical Journal Corp. Ltd, 2026)
Introduction: Interventional radiology oncology procedures require optimal sedation that ensures hemodynamic stability, respiratory safety, and adequate analgesia. Ketamine-propofol (ketofol) combines the sympathomimetic properties of ketamine with the sedative effects of propofol, offering potential advantages in this vulnerable population. This systematic review evaluates the role of ketofol in interventional radiology oncology procedures. Methods: A systematic review of 58 sources identified through screening based on predefined criteria including ketofol intervention, adult oncology patients undergoing interventional procedures, and appropriate study designs. Data were extracted on procedure context, patient characteristics, ketofol administration, comparator regimens, sedation effectiveness, safety outcomes, recovery parameters, and clinical recommendations. Results: Meta-analyses demonstrated that ketofol significantly reduces hypotension (RR 0.11-0.40), bradycardia (RR 0.34-0.47), and respiratory adverse events (RR 0.48-0.55) compared to propofol alone. Ketofol reduces propofol consumption by 30-65% and provides superior analgesia. However, ketofol increases neurological adverse events compared to propofol (RR 1.95-3.68) and may prolong recovery by 2-7 minutes. The 1:2 to 1:4 ketamine-to-propofol ratio appears optimal. Discussion: Ketofol demonstrates pharmacological synergy that addresses the specific needs of interventional radiology oncology patients, who often present with compromised cardiovascular status. The hemodynamic and respiratory advantages are well-established across diverse clinical contexts. However, direct evidence in interventional radiology oncology remains limited, with most studies excluding high-risk patients (ASA III-IV) typical of oncology practice. The trade-off between improved cardiorespiratory stability and increased neuropsychiatric effects requires individualized patient selection. Conclusion: Ketofol at 1:2-1:4 ratios represents a reasonable sedation strategy for interventional radiology oncology procedures where hemodynamic stability and respiratory safety are priorities. Future research should focus on high-risk oncology patients, optimal dosing for prolonged procedures, and head-to-head comparisons with dexmedetomidine-based regimens.